One-year Mortality Outcomes From the Advancing Cryptococcal Meningitis Treatment for Africa Trial of Cryptococcal Meningitis Treatment in Malawi. (1st June 2019) - Kanyama, Cecilia; Molloy, Síle F; Chan, Adrienne K; Lupiya, Duncan; Chawinga, Chimwemwe; Adams, Jack; Bright, Philip; Lalloo, David G; Heyderman, Robert S; Lortholary, Olivier; Jaffar, Shabbar; Loyse, Angela; et al.
Abstract: In Malawi, 236 participants from the Advancing Cryptococcal Meningitis Treatment for Africa trial were followed for 12 months. The trial outcomes reported at 10 weeks were sustained to 1 year. One-week amphotericin B plus flucytosine was associated with the lowest 1 year mortality (27.5% [95% confidence interval, 16.3 to 44.1]).